Pediatric chest‐abdomen‐pelvis and abdomen‐pelvis CT images with expert organ contours. Issue 5 (4th February 2022) - Jordan, Petr; Adamson, Philip M.; Bhattbhatt, Vrunda; Beriwal, Surabhi; Shen, Sangyu; Radermecker, Oskar; Bose, Supratik; Strain, Linda S.; Offe, Michael; Fraley, David; Principi, Sara; Ye, Dong Hye; et al.
Abstract : Purpose: Organ autosegmentation efforts to date have largely been focused on adult populations, due to limited availability of pediatric training data. Pediatric patients may present additional challenges for organ segmentation. This paper describes a dataset of 359 pediatric chest‐abdomen‐pelvis and abdomen‐pelvis Computed Tomography (CT) images with expert contours of up to 29 anatomical organ structures to aid in the evaluation and development of autosegmentation algorithms for pediatric CT imaging. Acquisition and validation methods: The dataset collection consists of axial CT images in Digital Imaging and Communications in Medicine (DICOM) format of 180 male and 179 female pediatric chest‐abdomen‐pelvis or abdomen‐pelvis exams acquired from one of three CT scanners at Children's Wisconsin. The datasets represent random pediatric cases based upon routine clinical indications. Subjects ranged in age from 5 days to 16 years, with a mean age of 7 years. The CT acquisition, contrast, and reconstruction protocols varied across the scanner models and patients, with specifications available in the DICOM headers. Expert contours were manually labeled for up to 29 organ structures per subject. Not all contours are available for all subjects, due to limited field of view or unreliable contouring due to high noise. Data format and usage notes: The data are available on The Cancer Imaging Archive (TCIA_ (https://www.cancerimagingarchive.net/ ) under the collection Pediatric‐CT‐SEG. The axial CT image slices for each subject are available in DICOM format. The expert contours are stored in a single DICOM RTSTRUCT file for each subject. The contour names are listed in Table 2. Potential applications: This dataset will enable the evaluation and development of organ autosegmentation algorithms for pediatric populations, which exhibit variations in organ shape and size across age. Automated organ segmentation from CT images has numerous applications including radiation therapy, diagnostic tasks, surgical planning, and patient‐specific organ dose estimation.